Administrative and Field Risk Analysis in the PGN Sales Division Using the FMEA Method - Ainur Zaki Yamami; Sumiati (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This study analyzes administrative and field operational risks in the Sales Operation Regional (SOR) III of PT Perusahaan Gas Negara (PGN) using the Failure Mode and Effect Analysis (FMEA) method. The objective of this research is to identify potential failure modes in customer service processes and determine risk priorities that may affect service quality and operational safety. Data were collected through observations, interviews, and documentation during an internship period, covering administrative activities and gas pipeline installation processes. The analysis shows that potential failures are concentrated in three main stages: customer data input, data verification at the head office, and gas pipeline installation. The results indicate that the data input stage has the highest risk level, with the loss of customer data forms recording the highest Risk Priority Number (RPN) value. Technical constraints during data verification and safety-related issues during gas installation were also identified, although with relatively lower RPN values. Overall, the application of the FMEA method provides effective insights for prioritizing corrective actions and improving the reliability, safety, and efficiency of natural gas service operations.